PRAGMALINGUISTIC FUNCTIONS OF DEICTIC UNITS IN UZBEKI AND ENGLISH LANGUAGES - Nurmatova Nilufar Ilkhamovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes in detail the pragmalinguistic functions of deictic units in Uzbek and English languages. Also, in the article, the semantic-programinguistic features of deictic units in English and Uzbek languages are compared and expressed using examples. Solutions to these aspects have been proposed in modern linguistics.